Marion Lane and the midnight murder - Willberg, T. A (Park Row Books, 2020)
"Late one night in April 1958, a filing assistant at Miss Brickett's receives a letter of warning, detailing a name, a time, and a place. She goes to investigate but finds the room empty. At the stroke of midnight, she is murdered by a killer she can't see--her death the only sign she wasn't alone. It becomes chillingly clear that the person responsible must also work for Miss Brickett's, making everyone a suspect. Marion Lane, a first-year Inquirer-in-training, finds herself drawn ever deeper into the investigation. When her friend and colleague is framed for the crime, to clear his name she must sort through the hidden alliances at Miss Brickett's and secrets dating back to WWII."--Publisher's description.